The significance of NGAL and KIM-1 proteins for diagnosis of acute kidney injury (AKI) in clinical practice - Kubrak, Tomasz; Podgórski, Rafał; Aebisher, David; Gala-Błądzińska, Agnieszka (European Journal of Clinical and Experimental Medicine, 2018)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Despite advances in medical care AKI (acute kidney injury) is associated with high morbidity and mortality. The lack of adequate early renal injury biomarkers is often a problem for an early AKI diagnosis. In recent years, numerous scientific studies have been carried out which reveal new urine and serum markers to assess the period of the kidney injury before revealing its late clinical effects. In most clinical settings, AKI is due to acute renal tubular necrosis which results in protein accumulation in urine. Determination of the concentrations of proteins such as NGAL (neutrophil gelatinase-associated lipocalin) and KIM-1 (kidney injury molecule-1) are of great significance in the diagnosis of AKI. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The purpose of the study was to review the literature about significance of NGAL and KIM-1 proteins for diagnosis of acute kidney injury (AKI) in clinical practice. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Materials and method. Analysis of Polish and foreign literature.